2020
DOI: 10.1186/s12879-020-05041-3
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological, clinical characteristics and drug resistance situation of culture-confirmed children TBM in southwest of China: a 6-year retrospective study

Abstract: Background: Sichuan is a province located in southwestern China, which have a higher incidence of tuberculosis (TB). This study aimed to analyze the epidemiological and clinical characteristics, as well as drug resistance in culture-confirmed children with Tuberculosis meningitis (TBM) in Southwest of China. Methods: We performed a retrospective study on children (< 14 years old) with cerebrospinal fluid (CSF) cultureconfirmed TBM between January 2013 and December 2018 at Public Health Clinical Center of Cheng… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
(21 reference statements)
0
12
0
Order By: Relevance
“…Owing to its remote geographical position and the limitations of local medical services, Sichuan has a high incidence of TB (approximately 100 cases per 100,000 people), [9] with the second highest TB caseload among the provinces in China. [10] The HIV testing coverage and HIV-positive case detection rates in Sichuan were estimated to be approximately 76% and 0.9%, respectively, as revealed in the TB report of China 2019 from the Center of Disease Control and Prevention of China. Nonetheless, another investigation in Sichuan showed that HIV testing was not universally available for outpatient TB cases; only 29.5% (3227/10,946) of cases had HIV test results.…”
Section: Yang Et Al • Medicine (2022) 101:48 Medicinementioning
confidence: 99%
“…Owing to its remote geographical position and the limitations of local medical services, Sichuan has a high incidence of TB (approximately 100 cases per 100,000 people), [9] with the second highest TB caseload among the provinces in China. [10] The HIV testing coverage and HIV-positive case detection rates in Sichuan were estimated to be approximately 76% and 0.9%, respectively, as revealed in the TB report of China 2019 from the Center of Disease Control and Prevention of China. Nonetheless, another investigation in Sichuan showed that HIV testing was not universally available for outpatient TB cases; only 29.5% (3227/10,946) of cases had HIV test results.…”
Section: Yang Et Al • Medicine (2022) 101:48 Medicinementioning
confidence: 99%
“…As the most lethal tuberculosis type, there have been more and more reports of RR/MDR-TBM in China and abroad in recent years. Some small sample of studies have shown that RR/MDR-TBM accounts for 12%-39.29% of TBM patients in western China, isoniazid resistant TBM reached 64.29% [13,14], even in children (untreated previously for tuberculosis) MDR and XDR accounted for 7.2% [15]. Although the sample size of the above studies is small, it also indicates that RR/MDR-TBM was not rare in China.…”
Section: Discussionmentioning
confidence: 88%
“…Some small sample size studies had shown that RR/MDR-TBM accounted for 12%–39.29% of TBM patients in western China, and the ratio of isoniazid-resistant TBM even reached as high as 64.29% [ 14 , 15 ]. Even in children with first-time TB infection, MDR and XDR accounted for 7.2% [ 16 ]. Although the sample size of these studies was small, it still indicated that RR/MDR-TBM is not a rare disease in China.…”
Section: Discussionmentioning
confidence: 99%